The Role of RNA Binding Proteins for Local mRNA Translation: Implications in Neurological Disorders - Thelen, Maximilian Paul; Kye, Min Jeong (Frontiers in Molecular Biosciences, 2020)
As neurons are one of the most highly polarized cells in our body, they require sophisticated cellular mechanisms to maintain protein homeostasis in their subcellular compartments such as axons and dendrites. When neuronal protein homeostasis is disturbed due to genetic mutations or deletions, this often results in degeneration of neurons leading to devastating outcome such as spinal muscular atrophy (SMA), amyotrophic lateral sclerosis (ALS) and fragile X syndrome (FXS). Ribonucleoprotein (RNP) complexes are macromolecular complexes composed of RNA binding proteins (RBPs) and their target RNAs. RBPs contain RNA binding domains and bind to RNA molecules via specific sequence motifs. RNP complexes have various functions in gene expression including messenger RNA (mRNA) trafficking, RNA processing and silencing. In neurons, RBPs deliver specific sets of mRNAs to subcellular compartments such as axons and dendrites to be locally translated. Mutations or deletions in genes coding for RNPs have been reported as causes for neurological disorders such as SMA, ALS and FXS. As RBPs determine axonal or dendritic mRNA repertoires as well as proteomes by trafficking selective mRNAs and regulating local protein synthesis, they play a crucial role for neuronal function. In this review, we summarize the role of well-known RBPs, SMN, TDP-43, FUS and FMRP, and review their function for local protein synthesis in neurons. Furthermore, we discuss their pathological contribution to the neurological disorders.